EDUCATIONAL INNOVATION: THE ROLE OF PROFESSIONAL TEACHERS IN IMPROVING THE QUALITY OF EDUCATION - Asnawan (International Journal of Teaching and Learning, 2024)
The capacity of educators to carry out their primary responsibilities as educators, such as the ability to organize, carry out, and innovate in the classroom, is known as teacher professionalism. In the process of educational innovation, teachers play a crucial strategic role, particularly when it comes to raising the standard of student learning. It goes without saying that a teacher must possess a variety of abilities, including social, educational, professional, and personality competency. Innovation in education will lead to changes in all areas, ensuring that the educational process is always tailored to the demands and circumstances of the moment. Teachers whose role is to create educational innovations can improve the quality of learning, can help explain educational problems and find ways out of the educational process either now or in the future. Apart from that, teachers who master technology will provide good teaching to students. The research method used in this article is a literature review. A variety of resources, such as periodicals, books, documents, the internet, and libraries, are available for literature study. The writing style that is employed is a literature review study, with an emphasis on the findings of writing about educational innovation, specifically the contribution of professional teachers to raising educational standards. This study addresses the function and proficiency of educators, educators and the problems associated with professionalism, and the significance of professional teacher creativity in raising educational standards.